Regression model of water demand for the city of Lodz as a function of atmospheric factors - Czesław Domański; Robert Kubacki (Statistics in Transition new series (SiTns), 2022)
One of the Sustainable Development Goals (Goal 6) set by the United Nations is to provide people with access to water and sanitation through sustainable water resources management. Water supply companies carrying out tasks commissioned by local authorities ensure there is an optimal amount of water in the water supply system. The aim of this study is to present the results of the work on a statistical model which determined the influence of individual atmospheric factors on the demand for water in the city of Lodz, Poland, in 2010-2019. In order to build the model, the study used data from the Water Supply and Sewage System Company (Zak±ad Wodoci\~nagów i Kanalizacji Sp. z o.o.) in the city of Lodz complemented with data on weather conditions in the studied period. The analysis showed that the constructed models make it possible to perform a forecast of water demand depending on the expected weather conditions.
Keywords: 519; water demand; atmospheric factors; regression model